Research Methodology and Management on Transport: Main Issues at the Final Stage of Russian Transport Sector Reforms - V. A. Persianov; A. A. Stepanov; T. M. Gainochenko (Управление)
The need for the development of fundamental economic science and the importance of scientific and pedagogical activity as a tool for improving national economies and international relations are substantiated. As one of the main reasons for the unsatisfactory state of the Russian transport complex the erroneous strategy and tactics of reforming the industry are seen, which in the early 1990s were adopted and brought to life without careful scientific study, did not take into account the national characteristics of the Russian economy, geopolitical and geo-economic interests of the country and its historical experience.The leading role of the State University of Management in preserving, developing and disseminating of fundamental knowledge in the field of economics and management in transport is underlined. The priority of scientific problems has been formulated and a plan for transport research has been developed. It is noted that the first and the main condition for the success of all the ongoing developments today is an attempt to delineate the boundaries of projects and programs for the development of transport, identify means, methods and opportunities for their implementation.The direction of the scientific specialization of the Department for management of the transport and expeditionary services of the State University of Management is proposed. It includes substantive formulation of scientific problems, the tracking and proactive evaluation of negative trends from the point of view of economic and national security in the transport of modern Russia. banking crises have serious consequences for the economy. The form of state participation in the process of overcoming a banking crisis and the extent of state involvement in solving the problems of insolvency of banks can be different: the government may restrict the measures to promote and support organization of private capital, to prefer the formal financial support of some banks, to take the banks under state control (control) or eliminate part of banks.